Thiacalixarene-supported Co24 nanocluster derived octahedral Co9S8 nanoparticles in N-doped carbon for superior Li-ion storage. (1st October 2019) - Han, Xu; Ai, Feixue; Wang, Xin; Chen, Baokuan; Wang, Lijuan; Bi, Yanfeng
Graphical abstract: Octahedral Co9 S8 nanoparticles embedded in N-doped carbon (Co9 S8 @CN ) has been fabricated by direct annealing the thiacalixarene-supported Co24 clusters for Li-ion storage. Abstract: Octahedral Co9 S8 nanoparticles embedded in N-doped carbon (Co9 S8 @CN ) are successfully synthesized by direct annealing thiacalixarene-supported Co24 clusters. The Co24 clusters served as not only sulfur and cobalt sources, but also provides main carbon and nitrogen. The Co9 S8 @CN composite achieved was used as electrode to fabricate Li-ion batteries (LIBs) exhibiting excellent rate capability and stable cycling performance. The first discharge capacity of the Co9 S8 @CN electrode is 881.5 mA h·g −1 and the charge capacity is 676.2 mA h·g −1, corresponding to the first Columbic efficiency of 76.7%. The Co9 S8 @CN electrode can deliver a stable discharge capacity of 618.1, 552.8, 489.9, 458.6, 394.4 and 328.6 mA h·g −1 at 0.1, 0.2, 0.5, 1.0, 2.0 and 3.0 A·g −1 . The discharge capacity of Co9 S8 @CN can maintain 406.5 mA h·g −1 after continuous 100 cycles at 1.0 A·g −1 .